La cura oltre la responsabilità: limiti dell’approccio jonasiano all’idea di sostenibilità - Pantaleone, Luca (Filosofia Morale/Moral Philosophy, 2024)
The concept of responsibility elaborated by Hans Jonas is at the basis of a precise idea of sustainability, centered on the scientific ability to make predictions and on the fear of the consequences that human actions can have on life. The purpose of the article is to investigate the limits of this approach, highlighting how the idea of a care connected to this kind of responsibility can limit individual freedoms and dangerously exclude the truth from the field of moral action. In particular, attention is given to the legitimacy of Jonas’s principle of responsibility, to its foundation and to the path he followed to set up an ethics of ends that is respectful of man’s duty to preserve life.